Fusarium DNA levels as compared to mycotoxin levels in Finnish and Estonian grain samples. - Yli-Mattila, T.; Rämö, S.; Tanner, R.; Loiveke, H.; Hietaniemi, V. (Plant Breeding and Seed Science, 2011)
In the present work Fusarium DNA levels of deoxynivalenol (DON)-producing F. graminearum and F. culmorum and T-2/HT-2-producing F. langsethiae and F. sporotrichioides were compared to DON and T-2/HT-2 levels in Finnish (19 oat samples) and Estonian (3 oat, 8 wheat and 9 barley) grain samples of the year 2008. The Finnish oat samples were selected based on high (<870 ppb) DON levels. Some of them also contained high levels of zearalenone (ZEN). The main aim was to find out, which Fusarium species is the main DON producer in oats in Finland. In Estonian grain sam- ples all mycotoxin levels were relatively low and below the EU limits. The highest ZEN levels were found in oat in Satakunta in Finland. This is the first study, in which F. graminearum has been found in Estonian grains. The correlation between F. graminearum DNA and DON levels in the combined Finnish and Estonian oat samples was higly significant (R2 = 0.88). In Finnish samples a significant correlation was also found between F. graminearum DNA and ZEN levels (R2 = 0.42). No correlation was found between F. culmorum DNA and DON levels in the combined Finnish and Estonian oat sam- ples. There was also a significant correlation between the combined T-2 and HT-2 and combined F. langsethiae and F. sporotrichioides levels (R2 = 0.38) in the combined Finnish and Estonian oat samples. According to our results F. graminearum is clearly the main DON producer in Finnish oat.